DHARMAYATRA IN THE DWIJENDRA TATTWA TEXT ANALYSIS OF RECEPTION - Rai Putra, Ida Bagus; Weda Kesuma, I Nyoman; Cika, I Wayan; Suastika, I Made (e-Journal of Linguistics; Vol. 5. Januari 2011 No. 2)
The object of the study is Dwijendra Text (hereinafter abbreviated to DT). It containsinteresting narrations and is importantly related to the dharmayatra, the holy religious journeymade by Dang Hyang Nirartha, the charismatic figure, in Bali, Lombok and Sumbawa. Beforethe analysis of reception was conducted, the corpus text of the DT texts completely andstructurally telling the religious journey made by Dang Hyang Nirartha was successfullydetermined. The analysis in this study was made to answer the following questions: what is thenarrative structure of the DT text; what are the enlightenment image entities of the dharmayatraof the DT text; how do people appreciate the dharmayatra of the DT text? The answers to thenarrative structure of the DT text; the image entities and the appreciation provided by people arethe main objectives of this study.The theories adopted in this study are the theory of reception introduced by Jauss, thetheory of semiotics introduced by Pierce and the theory of mythology introduced by Barthes. Asa qualitative study, the data needed were collected by the methods of observation, note taking,documentation and interview supported with a sound recorder and pictures. The results of theanalysis are informally presented, meaning that they are verbally described in the form of wordswhich are systematically composed based on the problems formulated in this study.The analysis of the narrative structure of the DT text contains narrative units which are inthe forms of theme, characters and plots. They all unite to form stories which are mythological,legendary, symbolic, hagiographic and suggestive in nature. Based on the analysis ofenlightenment image entities, it can be concluded that there are three basic entities leading to thecreation of the DT text. They are first enlightenment; second protection of Hinduism; and thirdconstruction of temple institutions. Based on the reception analysis, it can be concluded thatpeople, through their literary works, books, articles and websites, appreciate the discourse of thedharmayatra performed in Bali, Lombok and Sumbawa.The ten essential findings in this study can be described as follows. (1) The corpus text ofthe DT, which is in the form palm-leaf manuscript (lontar) and was obtained from GriyaBaturening Mambal, is kept as a collection at the Perpustakaan Lontar Fakultas SastraUniversitas Udayana (the Library of Palm-leaf Manuscripts of the Faculty of Letters, UdayanaUniversity). It is coded under no. 1514, kropak (box) no. 293. The DT text describes the real journey of Dang Hyang Nirarta, the great holy Hindu teacher, concretely, completely andstructurally. (2) As a literary text of history, the DT text has a highly narrative structure formedby theme, characters and plots which are unified in the forms of mythologies, legends,hagiographies, symbolisms and suggestive. (3) The dharmayatra made by Dang Hyang Nirartha,as described in the DT text, gave enlightenment and welfare to the kingdom and its people. (4)The teacher-learner (guru-sisya) teaching contained in the DT text may inspire a harmonious andethic relationship as far as teaching-learning process and priesthood are concerned. (5) Theconcern about the principle of unity in diversity taught by him may give relevant multiculturalperception of the current and upcoming way of life and Indonesianization. (6) The DT textreveals that those who belong to the Brahmin caste (Brahmana) have been descended from him.However, if viewed from the spiritual and priesthood points of view, he has been the source ofspirituality for Hindus, Buddhists, Moslems and those who do not belong to any religion (kapir).(7) The DT text shows that he is also called Pedanda/Bhatara Sakti Wawu Rawuh as he washighly powerful (sakti) and has symbolized the complete mastery of material and spiritualknowledge. (8) The religious journey (dharmayatra) made by him from Java to Bali, Lombokand Sumbawa aimed at protecting Majapahit Hinduism from being suppressed by Islam whichhad already spread all over the Archipelago. The protection of Hinduism and the construction ofthe temple institutions referred to the religious meaningfulness implemented by him. (9) Thisstudy explains that in Lombok he spread three religious teachings such as Gama Siki GamaThirtha, Gama Kalih Budha Paksa, and Gama Tiga Selame Metu Telu. (10) High appreciation isprovided to the dharmayatra he made in Bali, Lombok and Sumbawa. Such an appreciation orreception highly varies; in other words, it is expressed in the forms of literary works, books,articles and websites.